(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Maya Angelou is one of the prominent African American writers. She always writes on the themes like family, motherhood, race, displacement and journey very seriously and works to get free from the constraints of the so-called canonized versions of human ideals. She also looks to discover a world where she can establish her own unique viewpoints and the freedom of humanity. The underlying concepts of the existential crisis have played a significant role in how people have approached their work in various spheres of human experience. A lot of authors with African American ancestry have addressed these issues. I Know Why a Caged Bird Sings by Maya Angelou is filled with indications of estrangement and dissatisfaction. Maya Angelou’s in-depth examination of I Know Why the Caged Bird Sings, incorporated in this research is an attempt to represent and explain the concept of alienation. These writings’ poignant narratives call into question the crises of identity, gender and consciousness. The research concludes by demonstrating the struggles for acceptance and self-awareness and how they helped the character to grow into a stronger woman, driven by her sense of alienation.